Some more algorithms for Conway’s universal automaton - Melnikov, Boris; Dolgov, Vasily (Acta Universitatis Sapientiae. Informatica, 2014)
In this paper authors propose algorithms for constructing so called automaton COM(L) and prove that this automaton coincides, up to re-denoting states, with Conway’s universal automaton. We give some algorithms of constructing this automaton and consider some examples.